A wristband device for detecting human pulse and motion based on the Internet of Things. (15th October 2020) - Zhang, Yuan; Cui, Jian; Ma, Kai; Chen, Han; Zhang, Janey
Highlights: The IoT wireless intelligent health service terminal system was designed. A health-monitoring wristband and system was designed. The system realizes its real-time monitoring of physical health. The system provides an diagnosis basis for doctors. Abstract: The IoT (Internet of Things) wireless intelligent health service terminal system was designed and implemented realizes the real-time detection of patient's physical parameters. Designed and implemented a health-monitoring wristband and system that are easy to wear, accurate to detect, and easy to operate. It was determined that blood pressure, blood oxygen, pulse, exercise, and other sign parameters were the detection targets, and the overall plan design of the intelligent health service system was completed in combination with the characteristics of the detection targets. The mobile terminal of the mobile phone performs wireless communication with the detection device through the Bluetooth module, and the control device detects the biological information state of the human wrist pulse and movement at any time. After the detection result is processed by the system, it is fed back to the mobile terminal of the mobile phone in time.